2015
DOI: 10.3138/jvme.0914-094r1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Efficacy of a Canine Pelvic Limb Model Used to Teach the Cranial Drawer and Tibial Compression Tests in the Stifle Joint

Abstract: Canine cranial cruciate ligament rupture (CCLR) is the most common cause of pelvic limb lameness in dogs. CCLR results in palpable stifle instability secondary to cranial translation of the tibial relative to the femur, and it can be diagnosed during the orthopedic exam using the cranial drawer test (CDT) and tibial compression test (TCT). Accurate diagnosis of CCLR depends on the efficacy in performing these tests. In this study, two three-dimensional canine pelvic limb models were developed: one simulating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…13 Studies on the efficacy of teaching strategies based on the use of 2-D images and their associated 3-D structures found a significant improvement in the students' acquisition of knowledge when compared with the use of 2-D images only. 5,11,15,16 In our study, there was a trend towards better assessment scores for the students with no prior experience who used the 3-D models in their studies (i.e. the model group).…”
Section: Increase In Student Motivation Through the Use Of The Modelsmentioning
confidence: 55%
See 2 more Smart Citations
“…13 Studies on the efficacy of teaching strategies based on the use of 2-D images and their associated 3-D structures found a significant improvement in the students' acquisition of knowledge when compared with the use of 2-D images only. 5,11,15,16 In our study, there was a trend towards better assessment scores for the students with no prior experience who used the 3-D models in their studies (i.e. the model group).…”
Section: Increase In Student Motivation Through the Use Of The Modelsmentioning
confidence: 55%
“…9 A study evaluating the usefulness of a canine pelvic limb model used to teach cranial drawer and tibial compression tests in the stifle joint, confirmed that veterinary students were able to accurately diagnose canine cranial cruciate ligament rupture with the tibial compression test, following training on the model. 15 Similarly, a study involving the use of 3-D printed vertebrae models indicated that the models facilitated student learning of normal canine vertebral anatomy and improved their identification of canine spinal fractures. 16 In summary, 3-D models have been used to teach different techniques, with the common purpose of facilitating a better understanding of anatomical structures, increasing student engagement, and improving the students’ diagnostic and clinical skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer programs can convert cross‐sectional imaging, such as computed tomography (CT) or magnetic resonance imaging (MRI), to print physical models of a body part of interest. There are limited prior studies evaluating three‐dimensional‐printed anatomic models as supplemental aids to enhance performance of veterinary students 15–17 . Limitations of these studies included their evaluation of students on a volunteer basis (in which they knew their performance was not graded) and low number of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited prior studies evaluating three-dimensional-printed anatomic models as supplemental aids to enhance performance of veterinary students. [15][16][17] Limitations of these studies included their evaluation of students on a volunteer basis (in which they knew their performance was not graded) and low number of subjects.…”
mentioning
confidence: 99%